2016
DOI: 10.1515/bjdm-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Does gender influence color matching quality?

Abstract: This paper treats the stability of two superposed gravitating streams rotating about the axis transverse to the horizontal magnetic field. The critical wave number for instability is found to be affected by rotation for propagation perpendicular to the axis about which the system rotates. The critical wave number for instability is not affected by rotation when waves propagate along the axis of rotation. The critical wave number is affected by both the magnetic field and the streaming velocity in both cases. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…However in humans, two cone cell pigment genes are present on the X chromosome. If women happens to be heterozygous they could be tetra‐chromatic, which may provide them with an additional advantage in shade matching …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However in humans, two cone cell pigment genes are present on the X chromosome. If women happens to be heterozygous they could be tetra‐chromatic, which may provide them with an additional advantage in shade matching …”
Section: Discussionmentioning
confidence: 99%
“…If women happens to be heterozygous they could be tetra-chromatic, which may provide them with an additional advantage in shade matching. 13,28,29 Another factor which affect the shade selection is the lighting condition. It is recommended that the lighting condition of the doctor as well as the dental technician should be similar for an accurate shade reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…29 studies were in vitro and 8 were in vivo (Table 2). Out of the 37 articles included, 25 reported no significant difference in shade matching abilities between the sexes 1,5,9,14,15,17,19,30–47 . Of the 12 studies that found a significant difference, 11 reported that females had better scores in shade matching exercises 18,48–57 and 1 reported that males are better in color matching 16 …”
Section: Resultsmentioning
confidence: 99%
“…There were 12 studies that used the Vita classic shade guides, 5 of which reported significantly better performance of females 49–52,54 and 7 reported no significant difference, 1,5,19,42,44,45,47 Vita 3D Master was used by 12 studies, of which 4 reported significantly better performance of females 18,53,56,57 and 8 reported no significant difference 9,14,17,32–34,36,46 . Two studies used Vita linear guide 3D Master, both reporting no significant difference 30,39 . The combination of Vita classic and Vita 3D Master was employed by 5 studies, of which 3 reported no significant difference 37,40,43 and 2 reported significantly better female performance 48,55 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation